If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3y + 4) = 0 Reorder the terms: -1(4 + 3y) = 0 (4 * -1 + 3y * -1) = 0 (-4 + -3y) = 0 Solving -4 + -3y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -3y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -3y = 0 + 4 -3y = 0 + 4 Combine like terms: 0 + 4 = 4 -3y = 4 Divide each side by '-3'. y = -1.333333333 Simplifying y = -1.333333333
| 7z-2z=30 | | 0.12(y-9)+0.04y=0.14y-0.09(10) | | -5c(c-8c)= | | 2.8x=5.1 | | y/(-4)+5=15 | | 6t-2(5+4t)=5+2t | | .5x+.33(3x)=3 | | (2a+3b)(2a+3b)= | | x=7x-45 | | 72x^3-50x=0 | | 5/24+1/8=25/40 | | (2a+3b)2= | | S=4p+4q | | 4(m+9)=2(m-5)+2 | | 6x+5=-x+40 | | w-10=-1 | | 3x+5=(x-9) | | n+9=-14 | | -2h=22 | | 0.60+p=32 | | |x+4|=1 | | 2v^2=16 | | 2x-3=-17.5 | | -4a=-8 | | 0.33+x=22 | | -8-b=11 | | h-9=6 | | 5n+10(n+9)+25(n+30)=1000 | | 2(x+1)+3(x+5)=37 | | 15+0.25=20+0.05 | | 4x-9=6x+7 | | x+-3.2=6.7 |